PENGEMBANGAN MODEL PEMBELAJARAN SNOWBALL THROWING DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN BERBASIS PERMAINAN MONOPOLI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI MAN 2 MODEL MEDAN - Sayidah Latifah Hanum; Khairuddin Effendi Tambunan (Smart Education, 2026)
Abstract: This study aims to create a Snowball Throwing Learning Model combined with monopoly game-based learning media, in order to improve the learning outcomes of class XI students at MAN 2 Model Medan related to fiscal and monetary policy material. The method applied in this study is Research and Development (RandD) using the ADDIE model which includes steps, design analysis, development, implementation, and evaluation. The sample in this study were students from class XI F3 B and XI F4 B. Data were collected through various techniques including observation, documentation, questionnaires, and learning outcome tests. The research findings show that the resulting learning model is considered eligible, with validation from material experts reaching 80%, open material design experts 82.5%, and learning experts 80%. The effectiveness model is seen from the increase in the average post-test score in the experimental class which reached 85.83, compared to the pre-test score of only 55.16, with N-Gain showing a value of 0.665 in the moderate category. Furthermore, responses from teachers reached 100% and from students 87.3%, indicating that this learning model is highly practical to implement. Therefore, the Snowball Throwing Learning Model combined with the Monopoly game has proven effective, feasible, and practical in improving student learning outcomes. Keywords: Snowball Throwing; Monopoly Game; Learning Outcomes; Learning Model; ADDIE Abstrak: : Penelitian ini bertujuan untuk menciptakan Model Pembelajaran Snowball Throwing yang dikombinasikan dengan media pembelajaran berbasis permainan monopoli, demi meningkatkan hasil belajar siswa kelas XI di MAN 2 Model Medan terkait materi kebijakan fiskal dan moneter. Metode yang diterapkan dalam studi ini adalah Research and Development (RandD) dengan menggunakan model ADDIE yang mencakup langkah-langkah analisis, perancangan, pengembangan, penerapan, dan evaluasi. Sampel dalam penelitian ini adalah siswa dari kelas XI F3 B dan XI F4 B. Data dikumpulkan melalui berbagai teknik termasuk observasi, dokumentasi, angket, dan tes hasil belajar. Temuan penelitian menunjukkan bahwa model pembelajaran yang dihasilkan dianggap memenuhi syarat, dengan validasi dari ahli materi mencapai 80%, ahli desain bahan ajar 82,5%, dan ahli pembelajaran 80%. Keefektifan model terlihat dari peningkatan rata-rata nilai post-test pada kelas eksperimen yang mencapai 85,83, dibandingkan dengan nilai pre-test yang hanya 55,16, dengan N-Gain yang menunjukkan nilai 0,665 di kategori sedang. Selain itu, tanggapan dari guru mencapai 100% dan dari siswa sebesar 87,3%, menunjukkan bahwa model pembelajaran ini sangat praktis untuk diterapkan. Oleh karena itu, Model Pembelajaran Snowball Throwing yang digabungkan dengan permainan monopoli terbukti efektif, layak, dan praktis dalam meningkatkan hasil belajar siswa Kata Kunci: Snowball Throwing; Permainan Monopoli; Hasil Belajar; Model Pembelajaran; ADDIE